Alzheimer’s Disease and microRNA-132: A Widespread Pathological Factor and Potential Therapeutic Target - Zhang, Meng; Bian, Zhigang (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a common neurodegenerative disease in the elderly and is the most common type of dementia. AD is mostly gradual onset, and involves slow, progressive mental decline, accompanied by personality changes; the incidence of AD gradually increases with age. The etiology of AD is unknown, although it is currently believed to be related to abnormal deposition of amyloid β-protein (Aβ) in the brain, hyperphosphorylation of microtubule-associated protein tau, and the release of various cytokines, complements, activators and chemokines by cells. MicroRNAs (miRNAs) are a class of highly conserved non-coding RNAs that regulate gene expression at the post-transcriptional level, and manipulate the functions of intracellular proteins and physiological processes. Emerging studies have shown that miRNA plays an important role in regulating AD-related genes. MiR-132 is known as "NeurimmiR" due to its involvement in numerous neurophysiological and pathological processes. Accumulating pre-clinical results suggest that miR-132 may be involved in the progression of Aβ and tau pathology. Moreover, clinical studies have indicated that decreased circulating miR-132 levels could be used a potential diagnostic biomarker in AD. Here, we review the pathogenic role of miR-132 activity in AD, and the potential of targeting miR-132 for developing future therapeutic strategies.